Outcomes after hepatic resection and subsequent multimodal treatment of recurrence for multifocal hepatocellular carcinoma. Issue 11 (4th September 2013) - Kim, P. T. W.; Jang, J.‐H.; Atenafu, E. G.; Fischer, S.; Greig, P. D.; McGilvray, I. D.; Wei, A. C.; Gallinger, S.; Cleary, S. P.
Abstract : Background: The role of liver resection in patients with multifocal hepatocellular carcinoma (HCC) with well preserved liver function is controversial. This study was conducted to evaluate the outcomes of such patients. Methods: This was a retrospective analysis of patients who underwent liver resection for multifocal HCC between 1992 and 2011. Postoperative outcomes, survival and predictors of outcomes were analysed. Results: Of 46 patients who underwent hepatic resection for multifocal HCC, 38 had Barcelona Clinic Liver Cancer stage B disease. Major hepatectomy was performed in 27 patients, and major complications occurred in nine (20 per cent). The 90‐day postoperative mortality rate was 7 per cent. Overall 1‐, 2‐, 3‐ and 5‐year survival rates were 78, 64, 59 and 53 per cent respectively (median 70 months), whereas corresponding recurrence‐free survival rates were 53, 32, 30 and 27 per cent (median 14 months). Recurrence developed in 28 (61 per cent) of the 46 patients, affecting the liver only in 22. Three‐quarters of patients with recurrence underwent further therapy. Major hepatectomy (hazard ratio (HR) 0.37, 95 per cent confidence interval 0.14 to 0·95; P = 0·038), microvascular (HR 3·44, 1·35 to 8·74; P = 0·009) and macrovascular (HR 2·68, 1·11 to 6·43; P = 0·028) invasion, and cirrhosis (HR 3·15, 1·12 to 8·86; P = 0·029) were associated with overall survival. Microvascular invasion (HR 2·81, 1·06 to 7·40; P = 0·037), cirrhosis (HR 3·12, 1·41 to 6·88; P < 0·001) and bilobar disease (HR 2·93, 1·09 to 7·88; P = 0·033) were associated with recurrence‐free survival. Conclusion: In selected patients with multifocal HCC and well preserved liver function, long‐term survival is possible after liver resection and subsequent aggressive treatment of recurrence. Abstract : Favourable outcomes